Risk-factors for locally advanced rectal cancer relapse after neoadjuvant chemoradiotherapy: A single center experience - Stupar, Dragana; Jungić, Saša; Gojković, Zdenka; Berendika, Jelena; Janičić, Živojin (Medicine (Baltimore), 2023)
The overall prognosis of locally advanced rectal cancer (LARC) remains unsatisfactory due to a high incidence of disease relapse. The present understanding of the factors that determine the likelihood of recurrence is limited or ineffective. We aimed to identify the main risk factors influencing tumor relapse in LARC patients after neoadjuvant chemoradiotherapy (nCRT) and surgical treatment in a single center in Republika Srpska. Patients with stage II or stage III who received nCRT before surgery for primary rectal cancer at the Oncology Clinic, University Clinical Center of Republika Srpska from January 2017 and December 2022 were included in the study. We collected patient demographics, clinical stage and characteristics, neoadjuvant therapy, and surgical methods, along with the pathological response after treatment completion, and analyzed them to identify the risk factors for tumor relapse. Out of 109 patients diagnosed with LARC, 34 (31,2%) had tumor relapse. The median time to relapse was 54 months. Participants with clinical T4 stage had a significantly shorter relapse time compared to the patients with clinical T2/3 stage. Subjects with positive lymph nodes removed, perivascular and perineural invasion, intraoperative perforation and patients without ypN stage improvement had significantly shorter time to relapse. Subjects with T4 stage had more than 4 times higher risk of relapse than patients with clinical T2/3 stage. Higher clinical T stage was an essential risk factor for tumor relapse in LARC patients after nCRT and surgical treatment. Comprehensive understanding and identification of the risk factors for tumor relapse in LARC patients are crucial for improving their long-term outcomes.